Herbal flavonoids in preserving testicular physiology under oxidative stress: A bibliometric analysis of systematic reviews - Zulkifli, Baidillah; Fakri, Fajar; Gholib, Gholib; Akmal, Muslim; Adam, Mulyadi; Sabri, Mustafa; Lubis, Triva Murtina; Zainuddin, Zainuddin; Zulfitri, Zulfitri; Admi, Masda; Syah, Nanda Yulian; Usrina, Nora; Fajri, Fauzan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
Herbal antioxidants have gained attention recently as possible treatments for disorders of male reproductive function linked to oxidative stress because of their ability to neutralize free radicals.The investigation into herbal flavonoids for preserving oxidative stress-impaired testicular physiology has been effectively conducted through the visualization of bibliometric analysis. Bibliometric data of published papers collected from the PubMed and Scopus databases in 2018-2023. Network visualization was performed using VOSviewer software on the set keywords that occur (n=15). The literature review was conducted according to the research trends identified by the clusters that appeared in the network visualization. The result revealed that a total of 266 records have been published based on the specified search set keywords since 2018. Through the analysis of keywords, inclusion and exclusion criteria, and the relevant content of papers, 11 articles were identified as suitable for conducting a literature review. Network visualization revealed that the research falls into two general categories: (1) toxicity to the testicles caused by oxidative stress and (2) prevention of oxidative stress impact on tissue through herbal medicine. Examination of the paper's content revealed that certain antioxidant compounds from plants can stabilize free radicals in the testicles. These antioxidants include vitexin, diosmin, hesperidin, phenolic acids, naphthoquinones, fisetin, pachypodol, sciadopitysin, carvacrol, and morin. However, further research is needed to compare active antioxidant content in different herbal plants and identify optimal concentrations for therapeutic effects.